New Trade Unions of New Uzbekistan on The Path to Social Partnership - Kamolov Ilhomjon Ibrohimovich (Pubmedia Social Sciences and Humanities, 2025)
In today's world, where the processes of globalization and modernization are rapidly unfolding in social, economic, and spiritual spheres, this article briefly highlights the activities of the new trade unions of New Uzbekistan in ensuring social guarantees and social protection for workers through social partnership. This includes cooperation with employers, the development and implementation of measures aimed at the social protection of people engaged in non-standard forms of employment (such as those working in the informal sector, temporary and seasonal workers, etc.) and their family members, and the provision of targeted assistance to pensioners, people with disabilities, minors, elderly individuals living alone, and women in need of high-level social protection by including them in the “Ayollar daftari” (Women’s Register). It also reflects the role of trade unions in implementing democratic changes in all spheres of society and state life. The article concludes by discussing the prospects for trade unions in contributing to a more inclusive and equitable society in Uzbekistan